The Analysis of The Effect of Deposition Time on TSS Content Level - Neny Rochyani (Sriwijaya International Seminar on Energy-Environmental Science and Technology, 2014)
The experimental results obtained in laboratory conditions where the pH optimum was 7.3 at the best ratio of lime dose of 0.8 g / l to 50 minutes operating time. With the optimum conditions, subsequently measured the effectiveness of the deposition time on the water content of TSS and further improve the performance of lime in the water pH. From the test results and the measurements can be seen that the longer the settling time, the lower the TSS with the condition is the most influential on the fourth day. The measurement of the performance of lime in raising the pH of the mine water under conditions was known to remain effective in improving the conditions of pH. The most influential on the first day and the fourth day in which the pH of the mine water was on environmental quality standards.